RISK OF ACUTE RESPIRATORY INFECTION TRANSMISSION TO HEALTHCARE WORKERS DURING AEROSOL-GENERATING PROCEDURES - Hamad Hadi Mahdi Al Hattab, Amer Salem Hamad Al Sulaiman, Shaya Hamad Ali Albahri, Alhassan Hadi Hussain Alyami, Salem Mohammed Hussain Alrabie, Ghanem Mohammed Hussain Alrabie, Hussain Mahdi H Almuhamidh., Mohamed Ali Zaid Al Amri, Mahdi Mohammad Alyami,; Saleh Ali Saleh Almansour, Saeed Mohammed Ali Lesloom, Naser Mahdi Ali ALsallum, (Chelonian Research Foundation, 2022)
Introduction: The transmission of acute respiratory infections (ARIs) to healthcare workers (HCWs) during aerosol-generating procedures (AGPs) poses a significant risk, necessitating effective infection control measures. This systematic review aimed to evaluate the effectiveness Of various interventions designed to mitigate the risk of ARI transmission to HCWs during AGPs. Methods: A comprehensive search was conducted across PubMed, Embase, Scopus, and the Cochrane Library for interventional studies and clinical trials published in the last five years up to 2022. Studies were included if they assessed the risk of ARI transmission to HCWs during AGPs and evaluated the effectiveness of preventive measures. The primary outcomes included the incidence of ARI transmission, with adjusted risk ratios (aRRs) and confidence intervals (CIS) used to quantify the effectiveness of interventions. Results: Seven studies met the inclusion criteria, encompassing a range of interventions including enhanced personal protective equipment (PPE), procedural modifications, engineering controls, and educational programs. Notably, the use of fitted N95 respirators significantly reduced ARI transmission risk compared to surgical masks (aRR = 0.22, 95% CI: 0.09-0.54). Implementing portable high-efficiency particulate air (HEPA) filters in AGP areas was associated with a lower incidence Of ARI transmission (aRR = 0.53, 95% CI: 0.30-0.92). Educational interventions, although varied in design, consistently demonstrated a positive impact on reducing transmission risks. Conclusions: This review highlights the effectiveness of a multifaceted approach to preventing ARI transmission to HCWs during AGPs. Enhanced PPE, specifically fitted N95 respirators, combined with engineering controls such as HEPA filters, and comprehensive educational programs, significantly reduce the risk Of ARI transmission. These findings support the implementation of combined interventions to ensure the safety of HCWs in healthcare settings. Keywords: Aerosol-Generating Procedures, Acute Respiratory Infections, HealthCare Workers, Personal.